Using Edpuzzle interactive video to enhance listening skills - Nurwilis Elsa Zahara, Nurwilis Elsa Zahara; Yuliati (Universitas Negeri Semarang, 2025)
Listening comprehension is one of the most essential yet challenging skills in learning English as a Foreign Language (EFL). Despite its importance as a foundation for developing other language skills, listening often receives less instructional emphasis than grammar or vocabulary. Traditional listening instruction tends to be passive and lacks real-time feedback or learner control. This study reviews and explores the potential of Edpuzzle, an interactive video platform, to address these issues by offering pedagogical features aligned with multimedia learning principles. Grounded in Mayer's (2009) Cognitive Theory of Multimedia Learning, this study employs an integrative literature review method to synthesize relevant research published between 2015 and 2025. Findings from previous studies show that Edpuzzle enhances students' engagement, listening comprehension, and learning autonomy through features like embedded quizzes, self-paced playback, and immediate feedback. However, challenges remain, including limited infrastructure, teacher readiness, and familiarity with digital tools. The study concludes that Edpuzzle holds significant promise for transforming conventional listening instruction into a more interactive, reflective, and learner-centered process. This article contributes theoretically by reviewing and exploring how Edpuzzle aligns with current educational paradigms and suggests future empirical research and classroom application directions.